Pengaruh Konsentrasi Garam Dan Lama Fermentasi Terhadap Karakteristik Pikel Cabai Pimiento (Capsicum chinense) - Mardhatillah, Amelia; Ekawati, I Gusti Ayu; Indri Hapsari Arihantana, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 2 (2021): Jurnal ITEPA, 2021)
The research was conducted for the purpose of know the effect concentration of salt and fermentation time against the characteristic of pimiento pickle. The design used in this research was completely randomized design (RAL) factorials pattern, consisting of two factors .The first was the concentration of salt with concentration of 3 % , 6 % , and 9 % .The second factor was time consisting of two and three weeks .The whole treatment repeated three times to obtain 18 unit experiment .The data was analyzed with duncan test. The results of the study showed that the treatment of salt with 6 % concentration with 3 weeks fermentation was capable of producing pimento pickle with the best characteristic total criteria of  lactic acid bacteria 4.8x10 -6 CFU/ ml, pH 4.89, total acid 0.576 % and total dissolved solids 9.67 0 Brix.